THE IMPACT OF LEADERSHIP ON EMPLOYEE PERFORMANCE AT MUTIA SARI GENERAL HOSPITAL BENGKALIS REGENCY - Muhammad Erwin Soaduan Pohan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to determine the effect of leadership style on employee performance at Mutia Sari General Hospital in Bengkalis Regency. The method used is quantitative with data collection techniques through questionnaires to several employees of Mutia Sari General Hospital. Data analysis was carried out using validity, reliability, normality tests, simple linear regression, hypothesis testing, determination tests (R²), and t-tests. The results of the validity and reliability tests indicate that all research instruments are valid and reliable. The results of the normality test prove that the data are normally distributed. The results of simple linear regression and hypothesis testing indicate that leadership style has a positive effect on employee performance. The coefficient of determination (R²) value of 0.939 indicates that job training contributes 93.9% to improved performance, while the rest is influenced by other factors. The t-test produces a significant value (Sig. > 0.05), so it can be concluded that leadership style has a significant effect on employee performance at Mutia Sari General Hospital. Thus, leadership style is an important factor in improving employee performance.